Influence of the oxygen potential on the sintering of UO2–45% PuO2. Issue 13 (November 2015) - Noyau, S.; Audubert, F.; Martin, P.M.; Maitre, A.
Abstract: The manufacturing of U1− y Pu y O2± x mixed oxide fuel is usually based on the powder metallurgy process, and diffusion mechanisms occurring during the sintering of oxide ceramics are affected by the oxygen content of the atmosphere. In the present work, the sintering behaviour of the 55% UO2 + 45% PuO2 mixture was investigated as a function of the oxygen potential ranging from −524 to −355 kJ mol −1 . Due to the β − decay of 241 Pu present in the initial PuO2 powder, 0.72% of 241 Am/metal ratio is present within the sample. This study has shown the formation of U0.55 Pu0.45 O2− x solid solution whatever the oxygen potential applied. The apparent relative density of the ceramics varies with the oxygen potential and goes through a maximal value of 98.7%, for an oxygen potential ranging between −455 and −422 kJ mol −1 . The mean grain size and the intragranular porosity increase with the oxygen potential. A sintering map was established as a function of the oxygen potential. O/M ratio deduced from lattice parameters is close to 2 for all the samples, except for the more reductive conditions (−524 kJ mol −1 ) indicating an uncontrolled oxidation of the samples during cooling down, storage and samples preparation for XRD and XAS measurements. Pu distribution within U0.55 Pu0.45 O2± x ceramics obtained from powders mixing sintered at 1700 °C under an oxygen potential of around −425 kJ mol −1 was studied as a function of dwell time by means of XRD, EPMA and XAS analyses. The optimal homogeneity of the Pu distribution was achieved after 24 h sintering. XANES results confirmed the sample oxidation and could demonstrate the only presence of tetravalent Pu whereas Am is partially reduced.